Individualized Dosing of Fluoropyrimidine‐Based Chemotherapy to Prevent Severe Fluoropyrimidine‐Related Toxicity: What Are the Options? - Knikman, Jonathan E. (Clin Pharmacol Ther, 2020)
Fluoropyrimidines are widely used in the treatment of several types of solid tumors. Although most often well tolerated, severe toxicity is encountered in ~ 20–30% of the patients. Individualized dosing for these patients can reduce the incidence of severe fluoropyrimidine‐related toxicity. However, no consensus has been achieved on which dosing strategy is preferred. The most established strategy for individualized dosing of fluoropyrimidines is upfront genotyping of the DPYD gene. Prospective research has shown that DPYD‐guided dose‐individualization significantly reduces the incidence of severe toxicity and can be easily applied in routine daily practice. Furthermore, the measurement of the dihydropyrimidine dehydrogenase (DPD) enzyme activity has shown to accurately detect patients with a DPD deficiency. Yet, because this assay is time‐consuming and expensive, it is not widely implemented in routine clinical care. Other methods include the measurement of pretreatment endogenous serum uracil concentrations, the uracil/dihydrouracil‐ratio, and the 5‐fluorouracil (5‐FU) degradation rate. These methods have shown mixed results. Next to these methods to detect DPD deficiency, pharmacokinetically guided follow‐up of 5‐FU could potentially be used as an addition to dosing strategies to further improve the safety of fluoropyrimidines. Furthermore, baseline characteristics, such as sex, age, body composition, and renal function have shown to have a relationship with the development of severe toxicity. Therefore, these baseline characteristics should be considered as a dose‐individualization strategy. We present an overview of the current dose‐individualization strategies and provide perspectives for a future multiparametric approach.